Biochemical and Structural Evidence in Support of a Coherent Model for the Formation of the Double-Helical Influenza A Virus Ribonucleoprotein - Qiaozhen Ye (American Society for Microbiology, 2013)
ABSTRACT Influenza A virions contain eight ribonucleoproteins (RNPs), each comprised of a negative-strand viral RNA, the viral polymerase, and multiple nucleoproteins (NPs) that coat the viral RNA. NP oligomerization along the viral RNA is mediated largely by a 28-amino-acid tail loop. Influenza viral RNPs, which serve as the templates for viral RNA synthesis in the nuclei of infected cells, are not linear but rather are organized in hairpin-like double-helical structures. Here we present results that strongly support a coherent model for the assembly of the double-helical influenza virus RNP structure. First, we show that NP self-associates much more weakly in the absence of RNA than in its presence, indicating that oligomerization is very limited in the cytoplasm. We also show that once NP has oligomerized, it can dissociate in the absence of bound RNA, but only at a very slow rate, indicating that the NP scaffold remains intact when viral RNA dissociates from NPs to interact with the polymerase during viral RNA synthesis. In addition, we identify a previously unknown NP-NP interface that is likely responsible for organizing the double-helical viral RNP structure. This identification stemmed from our observation that NP lacking the oligomerization tail loop forms monomers and dimers. We determined the crystal structure of this NP dimer, which reveals this new NP-NP interface. Mutation of residues that disrupt this dimer interface does not affect oligomerization of NPs containing the tail loop but does inactivate the ability of NPs containing the tail loop to support viral RNA synthesis in minigenome assays. IMPORTANCE Influenza A virus, the causative agent of human pandemics and annual epidemics, contains eight RNA gene segments. Each RNA segment assumes the form of a rod-shaped, double-helical ribonucleoprotein (RNP) that contains multiple copies of a viral protein, the nucleoprotein (NP), which coats the RNA segment along its entire length. Previous studies showed that NP molecules can polymerize via a structural element called the tail loop, but the RNP assembly process is poorly understood. Here we show that influenza virus RNPs are likely assembled from NP monomers, which polymerize through the tail loop only in the presence of viral RNA. Using X-ray crystallography, we identified an additional way that NP molecules interact with each other. We hypothesize that this new interaction is responsible for organizing linear, single-stranded influenza virus RNPs into double-helical structures. Our results thus provide a coherent model for the assembly of the double-helical influenza virus RNP structure.